A novel Na2MoO4@CNT/Al–Zn–Mg–Cu composite with superior corrosion resistance and good mechanical properties: Effect of heat treatment - Jie Yang; Qing Li; Zhixiang Xiao; Zhengbin Wang; Zhenyu Liu; Bolv Xiao; Zongyi Ma; Yugui Zheng (Journal of Materials Research and Technology)
The development of Al–Zn–Mg–Cu alloys and their composites with good corrosion resistance and mechanical properties is highly demanding yet remains challenging. In this study, a new strategy of incorporating Na2MoO4 precipitants into bulk Al–Zn–Mg–Cu alloys using the inner cavity of opened carbon nanotubes (CNTs) combined with different heat treatments are employed to develop a novel Na2MoO4@CNT/7075 composite with superior corrosion resistance, high strength and good plasticity. The results show that as compared to the peak aging (PA) treatment, double aging (DA) and retrogression and re-aging (RRA) treatments can result in wider precipitation-free zone in the grain boundary with slightly larger precipitate phases. As a result, the DA- and RRA-treated Na2MoO4@CNT/7075 composite has good mechanical properties with high strength and relatively good elongation. Moreover, all the Na2MoO4@CNT/7075 composites have extraordinary corrosion resistance with a low corrosion rate (∼0.01 mm/y) in 0.6 mol/L NaCl solution and the highest resistance to intergranular corrosion (IGC depth of <5 μm) and exfoliation corrosion (EXCO rating of level N), regardless of the heat treatment. This is experimentally proved to originate from the pronounced surface enrichment of the Na2MoO4 precipitant released from exposed CNTs forming a protective surface film, which is independent of heat treatment, and therefore indicates that the aforementioned new strategy is highly effective to enhance corrosion resistance under different heat treatments. This work demonstrates that high-performance Al–Zn–Mg–Cu matrix composites with superior corrosion resistance and good mechanical properties can be developed by combining the new corrosion-resistance strategy and proper heat treatments.